2020
DOI: 10.1016/j.afjem.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Emergency Department preparedness in Nigeria: A prospective cross-sectional study

Abstract: Introduction Paediatric emergency medicine (PEM) is poorly developed in low and middle-income countries. The magnitude of challenges facing Paediatric Emergency Departments (PEDs) in Nigeria has not been well described. This study aimed to assess paediatric emergency care preparedness across PEDs in Nigeria. Methods This was a prospective cross-sectional study that utilized a self-administered questionnaire and a check list to assess three key domains (managerial, medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“… [15] In a recent nation-wide survey, Enyuma et al found that a majority of medical and nursing staff in paediatric EDs in Nigeria have not completed relevant subspecialty training. [16] Likewise, Abiodun et al found that less than a fifth of paediatric trainees in Nigeria had certification in a paediatric advanced life support (PALS) course. [3] This can undermine ECC preparedness and worsen the prevalent poor health indices in this setting.…”
Section: Introductionmentioning
confidence: 99%
“… [15] In a recent nation-wide survey, Enyuma et al found that a majority of medical and nursing staff in paediatric EDs in Nigeria have not completed relevant subspecialty training. [16] Likewise, Abiodun et al found that less than a fifth of paediatric trainees in Nigeria had certification in a paediatric advanced life support (PALS) course. [3] This can undermine ECC preparedness and worsen the prevalent poor health indices in this setting.…”
Section: Introductionmentioning
confidence: 99%